Hostname: page-component-745bb68f8f-kw2vx Total loading time: 0 Render date: 2025-02-11T11:51:16.140Z Has data issue: false hasContentIssue false

CUBES IN FINITE FIELDS AND RELATED PERMUTATIONS

Published online by Cambridge University Press:  15 July 2021

HAI-LIANG WU*
Affiliation:
School of Science, Nanjing University of Posts and Telecommunications, Nanjing210023, PR China
YUE-FENG SHE
Affiliation:
Department of Mathematics, Nanjing University, Nanjing210093, PR China e-mail: she.math@smail.nju.edu.cn
Rights & Permissions [Opens in a new window]

Abstract

Let $p=3n+1$ be a prime with $n\in \mathbb {N}=\{0,1,2,\ldots \}$ and let $g\in \mathbb {Z}$ be a primitive root modulo p. Let $0<a_1<\cdots <a_n<p$ be all the cubic residues modulo p in the interval $(0,p)$ . Then clearly the sequence $a_1 \bmod p,\, a_2 \bmod p,\ldots , a_n \bmod p$ is a permutation of the sequence $g^3 \bmod p,\,g^6 \bmod p,\ldots , g^{3n} \bmod p$ . We determine the sign of this permutation.

Type
Research Article
Copyright
© 2021 Australian Mathematical Publishing Association Inc.

1 Introduction

Investigating permutations over finite fields is an active topic in both number theory and finite fields. The Lagrange interpolation formula shows that each permutation over a finite field is in fact induced by a permutation polynomial. For example, let p be an odd prime and let a be an integer with $p\nmid a$ . Then $x \bmod p\mapsto ax \bmod p$ (for $x=0,1,\ldots ,p-1$ ) is a permutation over the finite field $\Bbb F_p=\Bbb Z/p\Bbb Z$ . Zolotarev [Reference Zolotarev12] showed that the sign of this permutation is precisely the Legendre symbol $({a}/{p})$ . Later, Lerch [Reference Lerch6] extended this result to the ring of residue classes modulo an arbitrary positive integer. In 2015, Brunyate and Clark [Reference Brunyate and Clark3] made a further extension to higher dimensional vector spaces over finite fields.

Recently, Sun [Reference Sun8, Reference Sun9] studied permutations involving squares in finite fields. In fact, let $p=2m+1$ be an odd prime. Let $0<b_1<\cdots <b_m<p$ be all the quadratic residues modulo p in the interval $(0,p)$ . Then clearly the sequence

$$ \begin{align*}1^2 \bmod p,\, 2^2 \bmod p,\ldots,m^2 \bmod p\end{align*} $$

is a permutation $\sigma _p$ of the sequence

$$ \begin{align*}b_1 \bmod p,\, b_2 \bmod p,\ldots, b_m \bmod p.\end{align*} $$

Let $\text {sign}(\sigma _p)$ denote the sign of $\sigma _p$ . Sun [Reference Sun8, Theorem 1.4] obtained

$$ \begin{align*}\textrm{sign}(\sigma_p)= \begin{cases} 1 &\mbox{if}\ p \equiv 3\bmod 8,\\ (-1)^{{(h(-p)+1)}/{2}} &\mbox{if} \ p\equiv 7 \bmod 8, \end{cases} \end{align*} $$

where $h(-p)$ denotes the class number of $\Bbb Q(\sqrt {-p})$ . Later, Petrov and Sun [Reference Petrov and Sun7] determined the sign of $\sigma _p$ in the case $p\equiv 1\ ({\textrm{mod}}\ 4)$ .

With this motivation, we consider permutations involving cubes in $\Bbb F_p=\Bbb Z/p\Bbb Z$ (where p is an odd prime). The case $p\equiv 2\bmod 3$ is trivial. Clearly in this case

$$ \begin{align*}\{x^3 \bmod p : x=0,1,\ldots,p-1\}=\Bbb Z/p\Bbb Z\end{align*} $$

and hence $x \bmod p\mapsto x^3 \bmod p\ (x=0,1,\ldots ,p-1)$ is a permutation $\tau _p$ over $\Bbb Z/p\Bbb Z$ . The sign of $\tau _p$ is a direct consequence of Lerch’s result [Reference Lerch6] and we have $\text {sign}(\tau _p)=(-1)^{{(p+1)}/{2}}$ (see [Reference Wang and Wu10, Theorem 1.2] for details).

Now we consider the nontrivial case $p\equiv 1\bmod 3$ . Let $p=3n+1$ be a prime with $n\in \Bbb N$ and let $g\in \Bbb Z$ be a primitive root modulo p. Let $0<a_1<\cdots <a_n<p$ be all the cubic residues modulo p in the interval $(0,p)$ . Then clearly the sequence

$$ \begin{align*}a_1 \bmod p, \,a_2 \bmod p,\ldots, a_n \bmod p\end{align*} $$

is a permutation $s_p(g)$ of the sequence

$$ \begin{align*}g^3 \bmod p,\, g^6 \bmod p,\ldots, g^{3n} \bmod p.\end{align*} $$

In order to state our result, we first introduce some notation. Let

$$ \begin{align*}\mathcal{P}:=\{0<x<p: x\ \text{is a primitive root modulo}\ p\}.\end{align*} $$

It is known (see [Reference Cox4]) that $4p$ can be uniquely written as

(1.1) $$ \begin{align} 4p=r^2+3s^2\quad (r,s\in\Bbb Z) \end{align} $$

with $r\equiv 1\bmod 3$ , $s\equiv 0\bmod 3$ and $3s\equiv (2g^n+1)r\bmod p$ . Let $\omega =e^{2\pi i/3}$ be a primitive cubic root of unity. As p splits in $\Bbb Z[\omega ]$ and $\Bbb Z[\omega ]$ is a principal ideal domain, we can write $p=\pi \bar {\pi }$ for some primary prime $\pi \in \Bbb Z[\omega ]$ with $({g}/{\pi })_3=\omega $ , where $\bar {\pi }$ denotes the conjugate of $\pi $ and the symbol $({\cdot }/{\pi })_3$ is the cubic residue symbol modulo $\pi $ . For convenience, we briefly recall the definition of the cubic residue symbol (see [Reference Ireland and Rosen5, Ch. 9] for details). For any $x\in \Bbb Z[\omega ]$ with $\pi \nmid x$ , there is a unique $i\in \{0,1,2\}$ such that $x^n\equiv \omega ^i\bmod {\pi \Bbb Z[\omega ]}$ . Hence, for any $x\in \Bbb Z[\omega ]$ with $\pi \nmid x$ , we define the cubic residue symbol $({x}/{\pi })_3$ by

$$ \begin{align*}\bigg(\frac{x}{\pi}\bigg)_3=\begin{cases} 1 &\mbox{if}\ x^n\equiv \omega^0\bmod {\pi\Bbb Z[\omega]},\\ \omega &\mbox{if} \ x^n\equiv \omega^1\bmod {\pi\Bbb Z[\omega]},\\ \omega^2 &\mbox{if}\ x^n\equiv \omega^2\bmod {\pi\Bbb Z[\omega]}. \end{cases}\end{align*} $$

We also define

(1.2) $$ \begin{align} \delta_p &:=|\{0<x<p/4: x\ \text{is a cubic residue modulo}\ p\}|, \end{align} $$
(1.3) $$ \begin{align} \alpha_p &:=|\{0<x<p/2: x\ \text{is a sixth power residue modulo } p\}|, \end{align} $$
(1.4) $$ \begin{align} \gamma_p &:=\bigg|\bigg\{0<x<p/2:\ \bigg(\frac{x}{p}\bigg)=1\ \text{and}\ \bigg(\frac{x}{\pi}\bigg)_3=\omega^2\bigg\}\bigg|, \end{align} $$

where $|S|$ denotes the cardinality of a set S.

With this notation, we now state our main result.

Theorem 1.1. Let $p=3n+1$ be a prime with $n\in \Bbb N$ .

  1. (i) If $p\equiv 1\bmod {12}$ , then

    $$ \begin{align*}|\{g\in\mathcal{P}: \textrm{sign}(s_p(g))=1\}|=|\{g\in\mathcal{P}: \textrm{sign}(s_p(g))=-1\}|.\end{align*} $$
  2. (ii) If $p\equiv 7\ ({\textrm{mod}}\ 12)$ , then $\textrm{sign}(s_p(g))$ is independent of the choice of g and

    $$ \begin{align*}\textrm{sign}(s_p(g))=(-1)^{\delta_p+(1+\alpha_p)(1+r)+(h(-p)+1-2\alpha_p)(2-r+3s)/4+s(1+\gamma_p)+(n-2)/4},\end{align*} $$
    where $h(-p)$ is the class number of $\Bbb Q(\sqrt {-p})$ .

Remark 1.2. For any primitive roots $g,g'$ modulo p, the product of $\text {sign}(s_p(g))$ and $\text {sign}(s_p(g'))$ is indeed equal to the sign of the permutation which sends the sequence

$$ \begin{align*}g^3\ \text{mod}\ p,\ g^6\ \text{mod}\ p,\ldots, g^{3n}\ \text{mod}\ p\end{align*} $$

to the sequence

$$ \begin{align*}g^{\prime3}\ \text{mod}\ p,\ g^{\prime6}\ \text{mod}\ p,\ldots, g^{\prime3n}\ \text{mod}\ p.\end{align*} $$

The signs of the permutations of this type are direct consequences of Lerch’s theorem [Reference Lerch6] and were investigated by Wang and the first author in [Reference Wang and Wu10, Theorem 3.2].

We will prove Theorem 1.1 in the next section.

2 Proof of Theorem 1.1

We first introduce some notation. Let $p=3n+1$ be a prime with $n\in \Bbb N$ and let $g\in \Bbb Z$ be a primitive root modulo p. Let $\omega =e^{2\pi i/3}$ be a primitive cubic root of unity.

As p splits in $\Bbb Z[\omega ]$ and $\Bbb Z[\omega ]$ is a principal ideal domain, we can write $p=\pi \bar {\pi }$ for some primary prime element $\pi \in \Bbb Z[\omega ]$ with $({g}/{\pi })_3=\omega $ , where $\bar {\pi }$ denotes the conjugate of $\pi $ and the symbol $({\cdot }/{\pi })_3$ is the cubic residue symbol modulo $\pi $ . For convenience, we use the symbol $\mathfrak {p}$ to denote the prime ideal $\pi \Bbb Z[\omega ]$ . Recall that from (1.1), $4p$ can be uniquely written as

$$ \begin{align*} 4p=r^2+3s^2\quad (r,s\in\Bbb Z) \end{align*} $$

with $r\equiv 1\bmod 3$ , $s\equiv 0\bmod 3$ and $3s\equiv (2g^n+1)r\bmod p$ .

Lemma 2.1 [Reference Berndt, Evans and Williams1, Corollary 10.6.2(c)].

For any k with $0<k<p$ , let

$$ \begin{align*}N(k):=|\{(x,y): 0<x,y<p, \,y^3-x^3\equiv k\bmod p\}|.\end{align*} $$

Then, with the above notation,

$$ \begin{align*}N(k)=\begin{cases} p+r-8 &\mbox{if}\ \bigg(\displaystyle\frac{k}{\pi}\bigg)_3=1,\\[6pt] (2p-r+3s-4)/2 &\mbox{if} \ \bigg(\displaystyle\frac{k}{\pi}\bigg)_3=\omega,\\[6pt] (2p-r-3s-4)/2 &\mbox{if}\ \bigg(\displaystyle\frac{k}{\pi}\bigg)_3=\omega^2. \end{cases}\end{align*} $$

For any k with $0<k<p$ , define

(2.1) $$ \begin{align} r_k:=\bigg|\bigg\{(x,y): 0<x<y<p,y-x\equiv k\bmod p, \,\bigg(\frac{x}{\pi}\bigg)_3=\bigg(\frac{y}{\pi}\bigg)_3=1\bigg\}\bigg|. \end{align} $$

We need the following result.

Lemma 2.2. We have

$$ \begin{align*}\sum_{0<k<p/2}r_{p-k}\equiv\bigg|\bigg\{0<x<p/4: \bigg(\frac{x}{\pi}\bigg)_3=1\bigg\}\bigg| \bmod 2.\end{align*} $$

Proof. From the definition,

(2.2) $$ \begin{align} \sum_{0<k<p/2}r_{p-k} = \bigg|\bigg\{(x,y): 0<x<y<p,\ y-x>p/2,\ \bigg(\frac{x}{\pi}\bigg)_3=\bigg(\frac{y}{\pi}\bigg)_3=1\bigg\}\bigg|. \end{align} $$

Replacing y by $p-y$ in the right-hand side of (2.2),

$$ \begin{align*} \sum_{0<k<p/2}r_{p-k} = \bigg|\bigg\{(x,y): 0<x,y<p,\ x+y<p/2,\, \bigg(\frac{x}{\pi}\bigg)_3=\bigg(\frac{y}{\pi}\bigg)_3=1\bigg\}\bigg|. \end{align*} $$

By symmetry,

$$ \begin{align*}\sum_{0<k<p/2}r_{p-k}\equiv\bigg|\bigg\{0<x<p/4: \bigg(\frac{x}{\pi}\bigg)_3=1\bigg\}\bigg| \bmod 2.\end{align*} $$

This completes the proof.

Now we define the following sets:

$$ \begin{align*} A_1:&=\bigg\{0<x<p/2: \bigg(\frac{x}{\pi}\bigg)_3=1\bigg\},\\ A_{\omega}:&=\bigg\{0<x<p/2: \bigg(\frac{x}{\pi}\bigg)_3=\omega\bigg\},\\ A_{\omega^2}:&=\bigg\{0<x<p/2: \bigg(\frac{x}{\pi}\bigg)_3=\omega^2\bigg\}. \end{align*} $$

For the following result, recall that $\mathfrak {p} = \pi \Bbb Z[\omega ]$ ) and $\alpha _p$ and $\gamma _p$ were defined in (1.3) and (1.4).

Lemma 2.3. Let $p\equiv 7\bmod {12}$ be a prime.

  1. (i) We have

    $$ \begin{align*}\prod_{x\in A_1}x\equiv(-1)^{1+\alpha_p}\bmod p.\end{align*} $$
  2. (ii) If

    $$ \begin{align*}\beta_p:=\bigg|\bigg\{0<x<p/2: \bigg(\frac{x}{p}\bigg)=1\ \text{and}\ \bigg(\frac{x}{\pi}\bigg)_3=\omega\bigg\}\bigg|,\end{align*} $$
    then
    $$ \begin{align*}\prod_{x\in A_{\omega}}x\equiv (-1)^{1+\beta_p}\omega^2\bmod {\mathfrak{p}}.\end{align*} $$
  3. (iii) We have

    $$ \begin{align*}\prod_{x\in A_{\omega^2}}x\equiv (-1)^{1+\gamma_p}\omega\bmod {\mathfrak{p}}.\end{align*} $$

Proof. (i) One can verify the following polynomial congruence:

$$ \begin{align*}\prod_{0<x<p,\,({x}/{\pi})_3=1}(T-x)\equiv T^{n}-1\bmod p.\end{align*} $$

Hence,

$$ \begin{align*}(-1)^{n/2}\bigg(\prod_{x\in A_1}x\bigg)^2\equiv -1\bmod p.\end{align*} $$

Since $p\equiv 3\bmod 4$ ,

$$ \begin{align*}\bigg(\prod_{x\in A_1}x\bigg)^2\equiv 1\bmod p.\end{align*} $$

Thus,

$$ \begin{align*}\prod_{x\in A_1}x\equiv(-1)^{n/2-\alpha_p}\equiv(-1)^{1+\alpha_p}\bmod p.\end{align*} $$

(ii) As in (i),

$$ \begin{align*}\prod_{0<x<p,\,({x}/{\pi})_3=\omega}(T-x)\equiv T^n-\omega\bmod{\mathfrak{p}}.\end{align*} $$

Hence,

$$ \begin{align*}\bigg(\prod_{x\in A_{\omega}}x\bigg)^2\equiv \omega\bmod{\mathfrak{p}}.\end{align*} $$

Noting that $\omega =(\omega ^2)^2$ is a quadratic residue modulo $\mathfrak {p}$ , by the definition of $\beta _p$ ,

$$ \begin{align*}\prod_{x\in A_{\omega}}x\equiv(-1)^{1+\beta_p}\omega^2\bmod{\mathfrak{p}}.\end{align*} $$

(iii) With essentially the same method as in (ii), one can verify (iii).

Let $\Phi _{p-1}(T)$ be the $(p-1)$ th cyclotomic polynomial and let

$$ \begin{align*}P(T):=\prod_{1\le i<j\le n}(T^{3j}-T^{3i}).\end{align*} $$

Lemma 2.4 [Reference Wu and She11, Lemma 2.5].

Let $G(T)$ be an integral polynomial defined by

$$ \begin{align*}G(T)=\begin{cases}(-1)^{(n-2)/4}\cdot n^{n/2}&\mbox{if}\ p\equiv3\bmod4, \\(-1)^{(n-4)/4}\cdot n^{n/2}\cdot T^{(p-1)/4}&\mbox{if}\ p\equiv1\bmod4.\end{cases}\end{align*} $$

Then $\Phi _{p-1}(T)\mid (P(T)-G(T))$ .

Now we are in a position to prove our main result.

Proof of Theorem 1.1.

From the definition,

$$ \begin{align*}\textrm{sign}(s_p)\equiv\prod_{1\le i<j\le n}\frac{g^{3j}-g^{3i}}{a_j-a_i}\bmod{\mathfrak{p}}.\end{align*} $$

We first consider the numerator. Since p splits completely in the cyclotomic field $\Bbb Q(e^{2\pi i/(p-1)})$ , it follows that $\Phi _{p-1}(T) \bmod p\Bbb Z[T]$ splits completely in $\Bbb Z/p\Bbb Z[T]$ . Also, the set of all primitive $(p-1)$ th roots of unity maps bijectively onto the set of all primitive $(p-1)$ th roots of unity in the finite field $\Bbb F_p=\Bbb Z/p\Bbb Z$ . Hence,

(2.3) $$ \begin{align} \Phi_{p-1}(T)\equiv \prod_{x\in\mathcal{P}}(T-x)\bmod{p}, \end{align} $$

where

$$ \begin{align*}\mathcal{P}:=\{0<x<p: x\ \text{is a primitive root modulo}\ p\}.\end{align*} $$

By Lemma 2.4 and (2.3),

$$ \begin{align*}\prod_{1\le i<j\le n}(g^{3j}-g^{3i})=P(g)\equiv G(g)\bmod p,\end{align*} $$

that is,

(2.4) $$ \begin{align} \prod_{1\le i<j\le n}(g^{3j}-g^{3i})\equiv \begin{cases}(-1)^{(n-2)/4}\cdot n^{n/2}\bmod p&\mbox{if}\ 4\mid p-3, \\(-1)^{(n-4)/4}\cdot n^{n/2}\cdot g^{(p-1)/4}\bmod p&\mbox{if}\ 4\mid p-1.\end{cases} \end{align} $$

By (2.4), for any $g'\in \mathcal {P}$ ,

$$ \begin{align*}\prod_{1\le i<j\le n}\frac{g^{3j}-g^{3i}}{(g^{'})^{3j}-(g^{'})^{3i}}\equiv \begin{cases} (g/g')^{{(p-1)}/{4}}\bmod p &\mbox{if}\ 4\mid p-1,\\ 1 \bmod p&\mbox{if} \ 4\mid p-3. \end{cases}\end{align*} $$

If $p\equiv 1\bmod 4$ , this implies that $\text {sign}(s_p(g))\cdot \text {sign}(s_p(g^{-1}))=-1$ and so

$$ \begin{align*}|\{g\in\mathcal{P}: \textrm{sign}(s_p(g))=1\}|=|\{g\in\mathcal{P}: \textrm{sign}(s_p(g))=-1\}|.\end{align*} $$

If $p\equiv 3\bmod 4$ , it is clear that $\text {sign}(s_p(g))$ is independent of the choice of g.

We now consider the denominator and assume that $p\equiv 3\bmod 4$ . From the definition of $r_k$ in (2.1), it is clear that

$$ \begin{align*} \prod_{1\le i<j\le n}(a_j-a_i)\equiv \prod_{0<k<p}k^{r_k}&\equiv(-1)^{\sum_{0<k<p/2}r_{p-k}}\cdot\prod_{0<k<p/2}k^{r_k+r_{p-k}}\\ &\equiv(-1)^{\delta_p}\prod_{0<k<p/2}k^{r_k+r_{p-k}}\bmod {\mathfrak{p}}, \end{align*} $$

where $\delta _p$ is defined in (1.2) and the last congruence follows from Lemma 2.2. From the definition of $r_k$ , one can verify that for $0<k<p$ ,

$$ \begin{align*} r_k+r_{p-k}=N(k)/9, \end{align*} $$

where $N(k)$ is defined in Lemma 2.1. Consequently,

$$ \begin{align*}\prod_{1\le i<j\le n}(a_j-a_i) \equiv (-1)^{\delta_p}\prod_{x\in A_1}x^{{p+r-8}/{9}}\prod_{y\in A_{\omega}}y^{{2p-r+3s-4}/{18}}\prod_{z\in A_{\omega^2}}z^{{2p-r-3s-4}/{18}} \bmod \mathfrak{p}.\end{align*} $$

By Lemma 2.3,

$$ \begin{align*} \prod_{x\in A_1}x^{{p+r-8}/{9}} &\equiv(-1)^{(1+\alpha_p)(1+r)}\bmod {\mathfrak{p}}, \\ \prod_{y\in A_{\omega}}y^{{2p-r+3s-4}/{18}}\prod_{z\in A_{\omega^2}}z^{{2p-r-3s-4}/{18}} &\equiv (-1)^{(\beta_p+\gamma_p)(-r+3s)/2+(1+\gamma_p)s}\omega^{2s/3}\bmod{\mathfrak{p}}. \end{align*} $$

Note that

$$ \begin{align*}\alpha_p+\beta_p+\gamma_p=|\{0<x<p/2: x\ \text{is a quadratic residue modulo}\ p\}|.\end{align*} $$

By the class number formula of $\Bbb Q(\sqrt {-p})$ (see [Reference Borevich and Shafarevich2, Theorem 4, page 346]),

$$ \begin{align*}|\{0<x<p/2: x\ \text{is a quadratic residue modulo}\ p\}|\equiv \frac{h(-p)+1}{2}\bmod 2,\end{align*} $$

where $h(-p)$ is the class number of $\Bbb Q(\sqrt {-p})$ . Thus,

(2.5) $$ \begin{align} \prod_{1\le i<j\le n}(a_j-a_i) \equiv (-1)^{\delta_p+(1+\alpha_p)(1+r)+(h(-p)+1-2\alpha_p)(2-r+3s)/4+s(1+\gamma_p)}\omega^{2s/3}\ \text{mod}\ \mathfrak{p}. \end{align} $$

By (2.4),

(2.6) $$ \begin{align} \prod_{1\le i<j\le n}(g^{3j}-g^{3i})\equiv (-1)^{(n-2)/4}\cdot n^{n/2}\bmod p. \end{align} $$

By the result in [Reference Cox4, Exercise 4.15]), $3$ is a cubic residue modulo p if and only if the equation $4p=X^2+243Y^2$ has integral solutions. With our notation in (1.1), this is equivalent to $s\equiv 0\bmod 9$ . We now divide the remaining proof into two cases.

Case I: $3$ is not a cubic residue modulo p. Since

$$ \begin{align*}\textrm{sign}(s_p)\equiv\prod_{1\le i<j\le n}\frac{g^{3j}-g^{3i}}{a_j-a_i}\equiv\pm1\bmod{\mathfrak{p}},\end{align*} $$

we must have $n^{{n}/{2}}\equiv \varepsilon \omega ^{2s/3}$ for some $\varepsilon \in \{\pm 1\}$ . Hence,

$$ \begin{align*}\varepsilon\equiv n^{3n/2}\equiv\bigg(\frac{-3}{p}\bigg)\equiv1\bmod {\mathfrak{p}}.\end{align*} $$

Combining this with (2.5) and (2.6),

$$ \begin{align*}\textrm{sign}(s_p(g))= (-1)^{\delta_p+(1+\alpha_p)(1+r)+(h(-p)+1-2\alpha_p)(2-r+3s)/4+s(1+\gamma_p)+(n-2)/4}.\end{align*} $$

Case II: $3$ is a cubic residue modulo p. In this case, $n^{n/2}=\pm 1$ and hence

$$ \begin{align*}n^{n/2}=n^{3n/2}\equiv \bigg(\frac{-3}{p}\bigg)=1\bmod{\mathfrak{p}}.\end{align*} $$

Combining this with (2.5) and (2.6),

$$ \begin{align*}\textrm{sign}(s_p(g))=(-1)^{\delta_p+(1+\alpha_p)(1+r)+(h(-p)+1-2\alpha_p)(2-r+3s)/4+s(1+\gamma_p)+(n-2)/4}.\end{align*} $$

This completes the proof.

Acknowledgements

We thank the referee for helpful comments. The first author would like to thank Professor Hao Pan for his encouragement.

Footnotes

This research was supported by the National Natural Science Foundation of China (Grant No. 11971222).

The first author was also supported by NUPTSF (Grant No. NY220159).

References

Berndt, B. C., Evans, R. J. and Williams, K. S., Gauss and Jacobi Sums (Wiley, New York, 1998).Google Scholar
Borevich, Z. I. and Shafarevich, I. R., Number Theory (Academic Press, New York, 1966).Google Scholar
Brunyate, A. and Clark, P. L., ‘Extending the Zolotarev–Frobenius approach to quadratic reciprocity’, Ramanujan J. 37 (2015), 2550.10.1007/s11139-014-9635-yCrossRefGoogle Scholar
Cox, D. A., Primes of the Form ${x}^2+n{y}^2$ : Fermat, Class Field Theory and Complex Multiplication (Wiley, New York, 1989).Google Scholar
Ireland, K. and Rosen, M., A Classical Introduction to Modern Number Theory, 2nd edn, Graduate Texts in Mathematics, 84 (Springer, New York, 1990).10.1007/978-1-4757-2103-4CrossRefGoogle Scholar
Lerch, M., ‘Sur un théorème de Zolotarev’, Bull. Internat. Acad. François Joseph 3 (1896), 3437.Google Scholar
Petrov, F. and Sun, Z.-W., ‘Proof of some conjectures involving quadratic residues’, Electron. Res. Arch. 28 (2020), 589597.10.3934/era.2020031CrossRefGoogle Scholar
Sun, Z.-W., ‘Quadratic residues and related permutations and identities’, Finite Fields Appl. 59 (2019), 246283.10.1016/j.ffa.2019.06.004CrossRefGoogle Scholar
Sun, Z.-W., ‘On quadratic residues and quartic residues modulo primes’, Int. J. Number Theory 16(8) (2020), 18331858.10.1142/S1793042120500955CrossRefGoogle Scholar
Wang, L.-Y. and Wu, H.-L., ‘Applications of Lerch’s theorem to permutations of quadratic residues’, Bull. Aust. Math. Soc. 100 (2019), 362371.10.1017/S000497271900073XCrossRefGoogle Scholar
Wu, H.-L. and She, Y.-F., ‘Jacobsthal sums and permutations of biquadratic residues’, Finite Fields Appl. 70 (2021), Article no. 101789.10.1016/j.ffa.2020.101789CrossRefGoogle Scholar
Zolotarev, G., ‘Nouvelle démonstration de la loi de réciprocité de Legendre,’ Nouv. Ann. Math. 11 (1872), 354362.Google Scholar